Gradient residual strain and stress distributions in a high pressure torsion deformed iron disk revealed by high energy X-ray diffraction. (15th March 2018) - Todt, J.; Keckes, J.; Winter, G.; Staron, P.; Hohenwarter, A.
Abstract: High energy X-ray diffraction is used to investigate for the first time the distribution of residual X-ray elastic stresses inside a high pressure torsion (HPT) deformed iron disk with a diameter and thickness of 30 and 8 mm, respectively. In the experiment, a dedicated conical slit system restricts the diffraction gauge volume in three dimensions to 0.45 mm 3, which is then used to scan the bulk sample cross-section in a non-invasive manner. Pronounced residuals stress gradients with maximal tensile stresses of 200 MPa are observed along radial and tangential directions and are correlated to the deformation gradient arising from HPT. Graphical abstract: Image 1